O GEIA e a aplicação da agroecologia na mediação entre a escola, a universidade e sociedade francana - Ferro, Ana Carolina Iozzi [UNESP]; Ritossa, Elaine Maria Silveira [UNESP]; Nogueira, Guilherme [UNESP]; Mello, Renan Segantini da Silva [UNESP]; Fonseca, Genaro Alvarenga [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This article’s purpose is to present the extension group GEIA -“Grupo de Incentivo a Educação Ambiental”, originated in Universidade Estadual Paulista, Campus of Franca - SP. This group has a pioneer and innovative project because, among all the UNESP campus, it is the only one to engage in the formation of an agroforest inside the university, through techniques that are not well spread in the country. along with and complementary to the agroforest, the group has another project, the environmental education project for children in a public elementary school, having it’s educational methods guided by the principles of horizontal and popular education. Thus, GEIA proves itself to be necessary inside the public university environment, once it has the fundamental social role of forming critical and conscious agents, aware of their transforming capacity, besides having the responsibility of bringing to the external society the academic and practical knowledge.

O presente artigo propõe-se a apresentar o grupo de extensão GEIA - Grupo de Inventivo a Educação Ambiental, da Universidade Estadual Paulista, Câmpus Franca - SP. Este possui um projeto pioneiro e inovador, por ser o único dentre os campi da UNESP a empenhar-se na formação de uma agrofloresta dentro da universidade, através de técnicas pouco difundidas no país. Unido e complementar à agrofloresta o grupo possui outro projeto, o de educação ambiental para crianças do Ensino Fundamental I em uma escola municipal, tendo seus métodos educacionais norteados pelos princípios da educação popular e horizontal. Dessa forma, o GEIA se mostra necessário dentro do ambiente da universidade pública, pois esta tem o papel social fundamental de formar agentes críticos e conscientes de sua capacidade de transformação, além de deter a responsabilidade de levar à sociedade externa partes do conhecimento acadêmico e prático.
Keywords: Communicative extension; Environmental education; Agroecology; Extensão comunicativa; Educação ambiental; Agroecologia